All Days 1996
DOI: 10.2118/37125-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluation of the Role of Drill Solids in Formation Damage and Reduced Horizontal Well Productivity

Abstract: This paper examines the role of drill solids in causing formation and completion damage in horizontal openhole completions. Drill solids are routinely kept to a minimum in drilling fluids, mainly to improve drilling properties. However, these drill solids, even at low concentrations, represent a significant source of insoluble particulates that become incorporated in the drill-in fluid filtercake. Not only is the potential for formation damage greater, but these filtercakes laden with insoluble drill solids ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The above method provides a means to assess the relative damage mechanisms associated with the selected RDF. However, if a sand-control screen and/or gravel are introduced, additional assessment/techniques are required to determine compatibility or damage as introduced by the residual filter cake deposited from an RDF system (Hodge 1997;Burnett et al 1996;Price-Smith et al 1998;Burton et al 1998). In this scenario, a base line test may be required that includes a screen coupon, gravel or both.…”
Section: Relatively Large Difference Between Thismentioning
confidence: 99%
“…The above method provides a means to assess the relative damage mechanisms associated with the selected RDF. However, if a sand-control screen and/or gravel are introduced, additional assessment/techniques are required to determine compatibility or damage as introduced by the residual filter cake deposited from an RDF system (Hodge 1997;Burnett et al 1996;Price-Smith et al 1998;Burton et al 1998). In this scenario, a base line test may be required that includes a screen coupon, gravel or both.…”
Section: Relatively Large Difference Between Thismentioning
confidence: 99%
“…It includes measurement of Flow Initiation Pressure (FIP) for cake lift-off and removal of external filter cake damage. FIP is controlled by the cake property, but also the formation permeability and internal damage [6][7][8][9][10] . Removal of filter cake is done either by natural cleaning with the formation drawdown pressure or by chemical treatments with conventional acids and oxidizers or more sophisticated products like enzymes [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Tests conducted in Joint Industry studies (CEA 73 etc) and in Conoco internal testing have shown that screen permeabilities can be reduced from hundreds of thousands of milliDarcies initially to less than 10 mD due to filter cake plugging. [1][2][3][4][5] In cases where formation collapse occurs, the filtercake material mixes with the formation sand and reduces hole/screen annular permeabilities to values that can be significantly less than reservoir permeability. For this reason, many operators perform acid washes to remove filtercake prior to flowing the well.…”
Section: Introductionmentioning
confidence: 99%
“…These acid washes can effectively remove filtercake, however they can also lead to corrosion problems if the acid cannot be effectively inhibited for the required acid/screen contact time. [2][3][4][5][6] Corrosion control is especially difficult in production wells subject to long shut-in periods prior to flow back. In a number of cases, concerns about screen corrosion have led to elimination of the acid wash stage and attendant poor well productivity.…”
Section: Introductionmentioning
confidence: 99%